Chlamydia trachomatis-Specific Human CD8(+) T Cells Show Two Patterns of Antigen Recognition - Matyszak, Malgosia K. (American Society for Microbiology, 2004)
Chlamydia trachomatis is an intracellular gram-negative bacteria which causes several clinically important diseases. T-cell-mediated immunity and the production of gamma interferon (IFN-γ) are known to be essential for the clearance of the bacteria in vivo. Here we have investigated CD8(+)-T-cell responses to C. trachomatis in patients with previous episodes of chlamydia infection. To isolate C. trachomatis-specific CD8(+)-T-cell lines, dendritic cells (DC) were infected with C. trachomatis and cocultured with purified CD8(+) T cells to generate C. trachomatis-specific CD8(+)-T-cell lines which were then cloned. Two patterns of recognition of C. trachomatis-infected cells by CD8(+)-T-cell clones were identified. In the first, C. trachomatis antigens were recognized in association with classical class I HLA antigens, and responses were inhibited by class I HLA-specific monoclonal antibodies. The second set of clones was unrestricted by classical HLA class I, and further studies showed that CD1 molecules were also not the restriction element for those clones. Both types of clones produced IFN-γ in response to C. trachomatis and were able to lyse C. trachomatis-infected target cells. However, unrestricted clones recognized C. trachomatis-infected cells at much earlier time points postinfection than HLA-restricted clones. Coculture of C. trachomatis-infected DC with the C. trachomatis-specific clones induced DC activation and a rapid enhancement of interleukin-12 (IL-12) production. Early production of IL-12 during C. trachomatis infection, facilitated by unrestricted CD8(+)-T-cell clones, may be important in ensuring a subsequent Th1 T-cell-mediated response by classical major histocompatibility complex-restricted CD4(+) and CD8(+) T cells.